Comparison of the Effectiveness of Compassion-Based Therapy and Relational Imagery Training on Post-Traumatic Growth in Women with Experience of Spousal Infidelity - Hasoumi , Meysam; Moghtader , ‌Leila; Akbari , Bahman (KMAN Counseling & Psychology Nexus, 2026)
The marital covenant is a highly prevalent human institution that is at times confronted with an issue known as infidelity or extramarital relationships. Extramarital relationships are among the factors that challenge family health and constitute one of the most significant threats to marital functioning, stability, continuity, and relational quality. Accordingly, the aim of the present study was to compare the effectiveness of compassion-based therapy and relational imagery training on post-traumatic growth in women who had experienced spousal infidelity. The present research employed a quasi-experimental method with a pretest–posttest control group design, along with a two-month follow-up phase. The statistical population consisted of all women who had been subjected to spousal infidelity and who presented through a public call and were referred by counseling centers in Shahinshahr, Isfahan, in 2022. From this population, 48 eligible volunteers were selected using a convenience sampling method and were included in the study. Ultimately, 48 participants (three groups of 16) were analyzed. The research instrument was the Posttraumatic Growth Inventory (PTGI) developed by Tedeschi and Calhoun. Data were analyzed using SPSS software and analysis of variance techniques. The results of the present study indicated that although both the compassion-based therapy group and the relational imagery training group demonstrated significant effectiveness at the posttest and follow-up stages in enhancing post-traumatic growth compared with the control group, and both interventions were effective, there was a statistically significant difference between the two intervention groups in terms of effectiveness at the posttest and follow-up stages. Compassion-based therapy was reported to be more effective in increasing post-traumatic growth among women with experience of spousal infidelity.